The art and science of 360-degree feedback - Lepsinger, Richard (Jossey-Bass, 2009)
More and more organizations are using 360-degree feedback to provide an opportunity to talk about key changes. This new edition of a best-selling title on the topic of 360-degree feedback is revised to reflect new research and relevant statistics, advances in technology, and an increasingly more global and virtual work environment.